Massonia amoena (Asparagaceae, Scilloideae), a striking new species from the Eastern Cape, South Africa - Martínez-Azorín, Mario; Pinter, Michael; Deutsch, Gerfried; Brudermann, Andreas; Dold, Anthony P.; Crespo, Manuel B.; Pfosser, Martin; Wetschnig, Wolfgang (Phytotaxa, 2014)
As part of an ongoing study towards a taxonomic revision of the genus Massonia Houtt., a new species, Massonia amoena Mart.-Azorín, M.Pinter & Wetschnig, is here described from the Eastern Cape Province of South Africa. This new species is characterized by the leaves bearing heterogeneous circular to elongate pustules and the strongly reflexed perigone segments at anthesis. It is at first sight related to Massonia jasminiflora Burch. ex Baker, M. wittebergensis U.Müll.-Doblies & D.Müll.-Doblies and M. saniensis Wetschnig, Mart.-Azorín & M.Pinter, but differs in vegetative and floral characters, as well as in its allopatric distribution. A complete morphological description of the new species and data on biology, habitat, and distribution are presented.